Pengembangan Media Pembelajaran Kelas Online untuk Guru SMA di Kabupaten Magetan - Musdholifah musdholifah; Dewie Tri Wijayati Wardoyo; Sri Setyo Iriani; Ulil Hartono; Achmad Kautsar (IKIP PGRI Bojonegoro, 2020)
ABSTRACTThe limited ability of teachers to manage instructional media using technology apparently also happened to teachers in Magetan District. Based on surveys and interviews with the Head of education, youth and sport department Magetan District, the problem of the low use of technology in learning was also experienced by teachers in Magetan District. Especially for high school teachers in Magetan Regency. One of the things that can be use by the world of education, especially teachers in implementing the learning process, is by using google classroom application as a media for online classroom learning. This application is still rarely even unknown to most teachers in Indonesia. The overall output shows the majority of teachers as participants have opened online classes (60.87%) and the remaining 39.13% only made a few meetings but did not run. The obstacle is the low motivation and consistency of the teachers in running online classes. The implementation of community service activities has been going well and smoothly. The results of the implementation of these activities all stages of the implementation of activities run as planned.Â Keywords: google classroom, teacher, online classÂ ABSTRAKTerbatasnya kemampuan guru dalam mengatur media pembelajaran dengan teknologi ternyata terjadi juga pada guru-guru di kabupaten Magetan. Berdasarkan survey dan wawancara dengan Kepala Dinas Pendidikan Pemuda dan Olahraga Kabupaten Magetan masalah rendahnya penggunaan teknologi dalam pembelajaran juga dialami pada guru-guru di Kabupaten Magetan. Terutama pada guru-guru SMA di Kabupaten Magetan. Salah satu hal yang bisa dimanfaatkan oleh dunia pendidikan terutama guru dalam melaksanakan proses pembelajaran yaitu dengan cara memanfaatkan aplikasi google classroom sebagai media pembelajaran kelas online. Aplikasi ini masih jarang bahkan belum diketahui oleh sebagian besar guru di Indonesia. Luaran keseluruhan menunjukkan mayoritas guru sebagai peserta telah membuka kelas online (60,87%) dan sisanya 39,13% hanya membuat beberapa pertemuan namun tidak berjalan. Adapun hambatan adalah masih rendahnya motivasi dan konsistensi para guru dalam menjalankan kelas online. Pelaksanaan kegiatan pengabdian kepada masyarakat sudah berjalan dengan baik dan lancar. Hasil dari pelaksanaan kegiatan tersebut semua tahapan pelaksanaan kegiatan berjalan sesuai dengan yang direncanakan.Â Kata Kunci : google classroom, guru, kelas online